An atypical anxious‐impulsive pattern of social anxiety disorder in an adult clinical population. Issue 4 (10th April 2014) - Mörtberg, Ewa; Tillfors, Maria; van Zalk, Nejra; Kerr, Margaret
<x xml:space="preserve">Abstract</x> An atypical subgroup of Social Anxiety Disorder (SAD) with impulsive rather than inhibited traits has recently been reported. The current study examined whether such an atypical subgroup could be identified in a clinical population of 84 adults with SAD. The temperament dimensions harm avoidance and novelty seeking of the Temperament and Character Inventory, and the Liebowitz Social Anxiety Scale were used in cluster analyses. The identified clusters were compared on depressive symptoms, the character dimension self‐directedness, and treatment outcome. Among the six identified clusters, 24% of the sample had atypical characteristics, demonstrating mainly generalized SAD in combination with coexisting traits of inhibition and impulsivity. As additional signs of severity, this group showed low self‐directedness and high levels of depressive symptoms. We also identified a typically inhibited subgroup comprising generalized SAD with high levels of harm avoidance and low levels of novelty seeking, with a similar clinical severity as the atypical subgroup. Thus, higher levels of harm avoidance and social anxiety in combination with higher or lower levels of novelty seeking and low self‐directedness seem to contribute to a more severe clinical picture. Post hoc examination of the treatment outcome in these subgroups showed that only 20 to 30% achieved clinically significant change.